Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Show all work to factor x4 − 10x2 + 9 completely.

Sagot :

Answer:

(x+1)(x-1)(x+3)(x-3)

Step-by-step explanation:

x4-10x^2+9

Group expression so that the coefficients of the x^2 terms add up to +9.

= x^4 -9x^2   - x^2+9

match coefficients in both groups

= x^4 -9x^2   - (x^2-9)

factor each group

= x^2 (x^2-9) - 1(x^2-9)

now factor out the common factor (x^2-9)

= (x^2-1)(x^2-9)

Finally, factor each quadratic factor

= (x+1)(x-1)(x+3)(x-3)

Step-by-step explanation:

Since both terms are perfect squares, factor using the difference of squares formula, a² - b² =(a+b)(a−b)  where a=x and  b=3.

(x+3)(x-3)(x+1)(x-1)